The Feasibility Study of Offshore Wind Energy Potential in Kijal, Malaysia: The New Alternative Energy Source Exploration in Malaysia. Issue 2 (June 2014) - Albani, A.; Ibrahim, M.Z.; Yong, K.H.
Nowadays, many countries have been endeavoring to explore and exploit the offshore wind energy in terms of solving the problem of limitations of onshore wind energy. Wind energy is one of potential alternative for generating electricity in Malaysia. The offshore wind speed is better compared to onshore, so there is more potential contribution by offshore wind power in terms of electricity generation. This paper provides a summary of the offshore wind resources of the Kijal, Malaysia by analyzing the QuikSCAT satellite data which is available and can be downloaded from the WindPRO application. Based on these datasets, wind resources are assessed, and economical efficiency is evaluated by means of the expected capacity factor. Research was conducted using WindPRO and WAsP software to assess the potential of wind energy along the South China Sea in Kijal, Terengganu. Seven models of the wind turbines with different rated power; 110kW, 225kW, 275kW, 600kW, 850kW, 1000kW and 1250kW are taken for energy and economic feasibility analyses. The wind turbine with rated power 850 kW was indicated as the best wind turbine for installation in Kijal based on its best capacity factor, 26.8% In economical aspect, Malaysia does not have Feed in Tariff (FiT) rates for offshore wind projects, thus the range of predicted FiT rates, RM 0.30 to RM 2.00 were tested by using Net Present Value (NPV) and Payback Period (PBP) calculation. Finally, the conducive FiT rates for wind projects with secured investment were identified and the rates were in range RM 0.80 to RM 1.38. The overall results suggest that the wind energy has a bright future for use as an alternative source for generating electricity in Kijal, Malaysia.